What is The Effectiveness of Early Versus Delayed Surgical Fixation of Orthopaedic Injuries on Mortality and Functional Outcomes in Multiply Injured Patients? : A Systematic Review - Kenny Yose Timisela (International Medical Journal Corp. Ltd, 2026)
Introduction: The optimal timing for surgical fixation of orthopedic injuries in multiply injured patients remains controversial, with conflicting evidence regarding early versus delayed intervention. This review synthesizes current evidence on the effectiveness of early compared to delayed surgical fixation on mortality and functional outcomes in polytrauma patients. Methods: A comprehensive review of 80 studies examining timing of surgical fixation in multiply injured patients was conducted. Studies included randomized controlled trials, cohort studies, systematic reviews, and meta-analyses. Early fixation was variably defined as within 24-72 hours, delayed beyond these cutoffs. Outcomes assessed included mortality, complications (ARDS, pneumonia, multiple organ failure), healthcare utilization, and functional outcomes. Results: Early definitive fixation was not associated with increased mortality in adequately resuscitated patients (1.4% vs 1.6%, p=0.78) (1). However, early surgery in specific high-risk populations—particularly thoracic spine fractures with hemoglobin <10 mg/dL—showed significantly increased mortality (p<0.01) (14). Early fixation consistently reduced ARDS (1.7% vs 5.3%, p=0.048) (1), pneumonia (8.6% vs 15.2%, p=0.07), hospital length of stay (10.5 vs 14.3 days, p=0.001), and ICU days (5.1 vs 8.4 days, p=0.006). Damage control orthopedics offered no survival advantage over early total care (OR 0.92) and increased complications (39). Functional outcome data were limited, though early spinal decompression improved neurological recovery (log OR 0.82, p<0.001) (18). Discussion: Benefits of early fixation depend on adequate resuscitation, with subclinical hypoperfusion (lactate ≥2.5 mmol/L) predicting poor outcomes (13). Injury pattern significantly influences optimal timing, with thoracic spine injuries requiring caution while lumbar and extremity fractures benefit from early intervention. Conclusion: Early fixation within 24-48 hours is safe and beneficial in adequately resuscitated polytrauma patients but should be avoided in those with subclinical hypoperfusion or specific high-risk injury combinations. A physiology-driven, injury pattern-specific approach optimizes outcomes.